Rise of the family cafe: a journey of resilience and community - Mhd. Sarif, Suhaimi; Ismail, Yusof; Abdul Wahid, Mohammad Fikri (IIUM Press, 2023)
This abstract tells the inspiring story of Sudin, a mining worker in Malaysia, who aspires to create a better future for himself and his family. Faced with financial struggles, Sudin decides to migrate to Perth, Australia, seeking better opportunities. With the blessings of his parents, Sudin embraces the challenges of starting anew in a foreign country. In Perth, Sudin and his wife, Aisha, establish Family Cafe—a symbol of hope, resilience, and community. Together with Aisha's father, Haji Ishak, they navigate setbacks and build a thriving halal establishment. Through dedication and support, they win the trust and appreciation of their customers and neighbors, becoming a pillar of the Muslim community. Despite challenges, Sudin, Aisha, and Haji Ishak remain steadfast in their commitment. They overcome supply chain issues, customer concerns, and labor shortages. Their determination attracts the admiration of respected figures like Sheikh Salleh and strengthens their resolve to persevere. Family Cafe becomes a platform for growth, employment, and community empowerment. Sudin and Aisha expand their vision, focusing on sustainability, menu innovation, and engaging with the community. They embrace technology, create opportunities for Muslim youth, and foster inclusivity. This story highlights the power of love, support, and unwavering belief in the face of adversity. Sudin's journey and the success of Family Cafe inspire others to pursue their dreams, overcome obstacles, and create positive change in their communities.